THE VILLAGE GOVERNANCE MODEL THAT EMPOWERS COMMUNITIES IN INDONESIA'S BORDER AREAS - Putri, Rizca Yunike (Journal of Urban Sociology, 2019)
The problems that arise in relation to the implementation of village government are human resource capacity and institutional capacity in community empowerment. It is undeniable that villages in the Border have diversity in terms of the capacity of the village human resources and village institutions. For established villages, the implementation of the Village Law and the PP Village does not raise serious problems that can actually provide space for innovation to improve the welfare of rural communities. However, another story is that villages with minimal capacity certainly need efforts so that the village government is able to do better things for its people. Especially community empowerment for poverty alleviation through increasing income of poor families. By using qualitative research methods, supported by in-depth interviews in data collection and supporting sekounder data, this study provides an illustration of how village government empowered communities in villages as well as Indonesia's border areas.Keywords: community empowerment, village government, border area